A study of the attitude toward the teaching profession of the Suan Dusit Rajabhat University students of the graduate diploma program in teaching profession - เผือดจันทึก สมยศ; กี่สุขพันธ์ เบญจวรรณ; เอี่ยมเสน สิทธิพร; ปิ่นจินดา พันพัชร (Journal of Educational Review Faculty of Education in MCU, 2019)
The purposes of this research were to identified the attitude of the teaching profession of the Suan Dusit Rajabhat University students who were study in the graduate diploma program in the teaching profession at the Suan Dusit University, and to compared the attitude of students who studied in the graduate diploma program in the teaching profession that was been classified by sex, age, grade point average, working experience, working place in public or private, working place in Bangkok or other provinces, and position. Population were 170 students who studied in the graduate diploma program in teaching profession at Suan Dusit University. The students who were registered in the semester 2 of the academic year 2018 derived all of population. The instrument of this research was the attitude questionnaire which employed to use collecting data. The attitude questionnaires were distributed to those students and they return back (87.06 percentages). Data was analyzed by percentages, mean, standard deviation, t-test independent (t-test), and one-way analysis of variance (One-way ANOVA). The research results found that: 1) The students’ attitudes toward the teaching profession found that it was very high level (M=4.39). When we considered in the detail, the research results show that the process of the instruction and teachers’ activities were the highest (M=4.48). Following was the objectives of curriculum and philosophy of curriculum (M=4.47 and M= 4.44 respectively). The lowest level was the curriculum structure (M-4.22). 2) The results of comparison of the attitude toward the teaching profession of the Suan Dusit Rajabhat University found that there were no statistical differences in the students’ attitude toward the teaching profession which were classified by sex, age, grade point averages, working experience, working place, working place in public or private, working place in Bangkok or other province, and position.